PENGEMBANGAN E-LEARNING UNTUK PEMBELAJARAN SEKOLAH NONFORMAL - Fahmi Irfan (Delta: Jurnal Ilmiah Pendidikan Matematika, 2019)
Non-formal education is a path of education outside of formal educational line made by the government to facilitate people who can’t take a formal education. Learning time on non-formal education is much less compared to formal education. Therefore, it becomes a problem for the people who take a non-formal education. In addition, the lack of learning innovations also become constraints in non-formal schools.The study developed E-learning based Moodle which contains learning materials, assignments, and the question of the test. It aimed to develop a valid and practical E-learning. This development research used the development model of Thiagarajan et al. The stages in this research were defining, designing, and developing.Based on the results of the study, obtained E-learning which could increase the learning time and provide innovations in non-formal school learning. Meanwhile, the average total aspect of all validators was 4.19. According to the validation criteria, it could be concluded that the developed E-learning was included in the valid category. After E-learning practical stated, then the E-learning was tested in XI graders of PKBM Al-Hikmah Tangkil Kulon. Based on the average questionnaire which was given to the learning community, the results were obtained x=3,31 after testing. Based on the criteria of practicality, it could be concluded that the developed E-learning was practical. This meant that the developed E-learning based Moodle was valid and practical.Non-formal education is a path of education outside of formal educational line made by the government to facilitate people who can’t take a formal education.Learning time on non-formal education is much less compared to formal education. Therefore, it becomes a problem for the people who take a non-formal education. In addition, the lack of learning innovations also become constraints in non-formal schools.The study developed E-learning based Moodle which contains learning materials, assignments, and the question of the test. It aimed to develop a validand practical E-learning. This development research used the development model of Thiagarajan et al. The stages in this research were defining, designing, and developing.Based on the results of the study, obtained E-learning which could increase the learning time and provide innovations in non-formal school learning. Meanwhile, the average total aspect of all validators was 4.19. According to the validation criteria, it could be concluded that the developed E-learning was included in the valid category. After E-learning practical stated, then the E-learning was tested in XI graders of PKBM Al-Hikmah Tangkil Kulon. Based on the average questionnaire which was given to the learning community, the results were obtained after testing. Based on the criteria of practicality, it could be concluded that the developed E-learning was practical. This meant that the developed E-learning based Moodle was valid and practical.